2006
DOI: 10.1007/s11664-006-0131-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport properties of single GaN and InN nanowires

Abstract: The transport properties of single GaN and InN nanowires grown by thermal catalytic chemical vapor deposition were measured as a function of temperature, annealing condition (for GaN) and length/square of radius ratio (for InN). The as-grown GaN nanowires were insulating and exhibited n-type conductivity (n ; 2 3 10 17 cm ÿ3 , mobility of 30 cm 2 /V s) after annealing at 700°C. A simple fabrication process for GaN nanowire field-effect transistors on Si substrates was employed to measure the temperature depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 36 publications
3
35
1
Order By: Relevance
“…This was an interesting observation, based on which we assumed a unique radius-dependent mobility μ e (r ) for the NWs, which enabled us to extract mobility for many different diameters even from devices that contain multiple NWs (see the discussion below). Although dependence of NW conductance on diameter has been proposed earlier [23][24][25], to the best of our knowledge, dependence of mobility on NW diameter has not been proposed or investigated so far, mainly due to the difficulty in determining carrier mobility in InN NWs (through back-gate modulation of charges in an FET configuration) arising out of high carrier density [11,13].…”
Section: ∼850mentioning
confidence: 99%
See 2 more Smart Citations
“…This was an interesting observation, based on which we assumed a unique radius-dependent mobility μ e (r ) for the NWs, which enabled us to extract mobility for many different diameters even from devices that contain multiple NWs (see the discussion below). Although dependence of NW conductance on diameter has been proposed earlier [23][24][25], to the best of our knowledge, dependence of mobility on NW diameter has not been proposed or investigated so far, mainly due to the difficulty in determining carrier mobility in InN NWs (through back-gate modulation of charges in an FET configuration) arising out of high carrier density [11,13].…”
Section: ∼850mentioning
confidence: 99%
“…An intriguing property of InN NWs observed in several past studies is the variation in conductance with NW diameter [23][24][25][26]. While some studies reported an increase in conductance with a decrease in NW diameter [23], and proposed theoretical models for the behavior [24], other studies found that the conductance can decrease with a decrease in NW diameter [25,26].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…2,[4][5][6][7] Among the semiconductor nanowires, indium-based III-V semiconductors, such as InN, InAs and InSb, are known to have high conductivity and extremely high electron mobility. [8][9][10][11][12][13] Thus, it is of significant interest to investigate their quantum transport properties in order to evaluate them as the future building blocks for high-speed electronic devices. Figure 1c.…”
Section: Table Of Content Graphicmentioning
confidence: 99%
“…3 shows the result of mobility limited by SRS versus electron density. The value of three dimensional electron density of GaN nanowire is usually in the range 10 17 -10 18 cm -3 [11]. Mobility goes up with electron density increasing, for the reason that higher electron density indicate stronger screen effect, which is same as GaN heterojunction [7].…”
Section: Theoretical Models and Methodsmentioning
confidence: 99%